Basketball Learning Model Development Through MLM (Mobile Learning Media) Based on Android - Andi Nurabady; Devi Catur Winata (Journal Physical Education, Health and Recreation, 2021)
The long-term objective of this research is expected to be able to overcome the problems that have occurred so far in the world of education, especially physical education that occurs in the field of basketball material, both in the form of teaching methods of teachers / lecturers which are always monotonous so that students are not interested in sports lessons on basketball or facilities and infrastructure that are not provided at school / on campus so that this research is able to answer every problem that occurs in the field, especially when the problem increases with the Covid-19 pandemic, where learning methods change from face-to-face to online. Therefore, this researcher provides a solution by learning through Android-based MLM (Mobile Learning Media).The specific objective of this research is to develop a basketball learning model with an Android-based MLM (Mobile Learning Media) system that launches a basketball learning application via Android that can be downloaded by anyone and learning becomes easier. With the development of this method, it is hoped that it can provide solutions to teachers / lecturers, especially basketball lecturers in providing material to students during the current pandemic.